Biogenic Amines in Neurotransmission and Human Disease - Uçar, Ahmet (IntechOpen, 2019)
Drawing on the expertise of experienced researchers in neurotransmission and catecholamines, this book provides a brief overview of the latest knowledge in the field. The book contains an introductory chapter that aims to explain the subsequent four chapters for researchers who are new to the field.